PENINGKATAN KEMAMPUAN BERBAHASA ANAK MELALUI METODE COOPERATIVE LEARNING PADA TAMAN KANAK-KANAK PGRI UJUNG INDAH - Murniati Murniati; Arna Bahar; Isnawati Zainuddin (Universitas Negeri Makassar, 2021)
The purpose of the research is to improve the language skills of students of group B PGRI Ujung Indah through the application of cooperative learning methods. The research uses a qualitative approach, a type of Classroom Action Research. Data collection methods are observation and documentation. The target of the study was 15 children consisting of 7 men, 8 women, and 1 educator. From the results of research on children's language skills. Cycle I of the first meeting the average value is 2.07 and the second meeting is 2.40. Cycle II increases the average value to 3.33. The second meeting was 3.60. The indicator of a child's vocabulary wealth in cycle I of the first meeting is 1.67, at the second meeting is 2.60. In cycle II there is an increase. The first meeting of the average score was 2.80 and the second meeting was 3.13. On the indicator of the child's ability to tell the content of the story about the picture in the sequence, cycle I of the first meeting of the average score is 1.87, the second meeting of the average score of the protege is 2.33. In cycle, II occurs the first meeting of the first meeting the average value of the protégé is 2.93. The second meeting was at 3.20.